Perceptions on the various messages about Pearl Farm Beach Resort a study of press releases as a public relations tactic - Guinomla, Sittie Mohmina A.
Pearl Farm Beach Resort has become one of the most well-known tourist destinations in the Philippines. The beach resort employed various strategies and tactics in order to attain such prestige and reputation. Coupled with this is the resort's Public Relations methods that deliberated create and provide its internal and external publics a means of getting to know more about the resort and finding out its recent affairs. A part of the Public Relations Tactics is the utilization of PR Tools. In this case, this study delimited such PR tools into one-regular newspaper press releases, as basis for analysis. Through the newspaper press releases, this study aims to identify and analyze the respondents' perceptions regarding the various messages that are sent by the Pear Farm Beach Resort to its audience. Since we are also in view of the resort's images, the study will help foster and develop a greater comprehension on how corporation work. And this, specifically saying, depending on the images that are being projected in the press releases. The Pear Farm Beach Resort and its press releases for the year 2007 is the primary source of data and information for this study. In this study, there were 21 respondents, which are basically comprised of the 4th year BA Communication Arts students of the University of the Philippines Mindanao for the Academic Year 2007-2008. these respondents were asked to answer six (6) sets of survey questionnaires that were prepared by the researcher. The questionnaires included questions pertaining to the respondents' perception towards the ten (10) press releases that were presented to them. Such questions were based on the five (5) categories the corresponding press releases belong namely: events, trips, lifestyle and leisure, promotions and advertisements, and person. Most of audience used to have this notion that Pear Farm caters only to the people who belong to the higher income strata. After reading to 10 press releases, their notions were even heightened, that they deemed it as a very high end resort wherein only the elites can afford to be at Pear Farm. Through the questionnaires, data gathered and the help of Agenda Setting Theory, this study was able to find out and explain that the respondents' preconceived notions towards the aforementioned beach resort were reinforced even more. With this, we can also see how print media became a very potent means of shaping one's idea and how it can greatly establish perceptions that can affect how one sees the image of what was being projected on the media.